Kajian Fonologis Kesalahan Sistematis pada Presentasi Makalah Mahasiswa Universitas Mataram - Adiprasetio Prabowo; Moh. Zalhairi (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This article is entitled "Systematic Errors in Speech Production in the Presentation of Papers of the Indonesian Language and Literature Education Study Program, Mataram University (Phonological Studies). "The problem of this research is how are the forms of systematic errors in speech production and symptoms of systematic errors in speech production (phonological studies) that are found? The method of determining the research subject was carried out by determining the population of all PBSI Unram semester III students of 4 classes. The sample is regular morning class students, namely class III C and III D. Class III C consists of 40 students with details of 19 male and 21 female, while Class III D consists of 43 students with details of 20 male and 23 female. By using a purposive sampling technique. Data collection methods are observation and listening. Based on the data analysis, the conclusions were obtained: that was found a form of systematic error in fonts. The form of a systematic error in speech production namely changing the font by 13 words, removing the font by 12 words, adding the font by 3 words. Of the three forms of systematic font error, the data that many researchers found changed in the font. The researcher did not find any systematic errors in the phoneme form. NextThe symptom of systematic error in speech production (phonological study) with the most intense was the symptom of anaptyxis error of 5 words and the symptom of dissimilation error of 5 words.